Analisis Faktor Pendorong Keputusan Pembelian melalui Aplikasi Gofood pada Masyarakat Kota Batam - Ayu Puspitasari; Putri Else Tiara (Journal of Applied Business Administration, 2023)
The purpose of this study is to analyze the factors driving purchasing decisions through the GoFood application in the people of Batam City. The population in this study are people from several sub-districts in Batam City. This type of research is quantitative research with data collection techniques using questionnaires. The method in analyzing the data used is factor analysis. The results of this study indicate that there are factors that encourage purchasing decisions through the GoFood application in the people of Batam City.